2017
DOI: 10.1186/s40170-017-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of triple-negative breast cancer cells reveals metabolic vulnerabilities

Abstract: BackgroundAmong breast cancers, the triple-negative breast cancer (TNBC) subtype has the worst prognosis with no approved targeted therapies and only standard chemotherapy as the backbone of systemic therapy. Unique metabolic changes in cancer progression provide innovative therapeutic opportunities. The receptor tyrosine kinases (RTKs) epidermal growth factor receptor (EGFR), and MET receptor are highly expressed in TNBC, making both promising therapeutic targets. RTK signaling profoundly alters cellular meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 72 publications
11
117
1
Order By: Relevance
“…Metabolism can directly impact cellular epigenetic landscapes and alter responses to chemo-therapeutics 72 . In particular, acetylation of histones relies on the availability of the universal acetyl donor metabolite acetyl-CoA, which is biosynthesized by breakdown of carbohydrates through the glycolytic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolism can directly impact cellular epigenetic landscapes and alter responses to chemo-therapeutics 72 . In particular, acetylation of histones relies on the availability of the universal acetyl donor metabolite acetyl-CoA, which is biosynthesized by breakdown of carbohydrates through the glycolytic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting our findings, Lanning et al . recently reported that the TCA cycle metabolite 2‐oxoglutaric acid, a precursor of glutamate, was significantly reduced upon treatment with the selective MET inhibitor capmatinib in two TNBC mesenchymal‐like cell lines MDA‐MB‐231 and Hs578. Similarly, TCA cycle and central carbon metabolites such as aspartate, fumarate, and malate were decreased as well following erlotinib treatment .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Only few studies on breast cancer cell metabolism have been reported. [4][5][6] Only few studies on breast cancer cell metabolism have been reported.…”
mentioning
confidence: 99%